Performance assessment of feedlot cattle receiving two or three implants - Hidalgo, Jorge; García Muñiz, José G.; Lunesu, Mondina F.; Cesarani, Alberto; Atzori, Alberto S.; Espino, Marco A.; Salcedo, Roberto; Toledo, Eric; Gonzalez, John (Frontiers in Animal Science, 2026)
Our objective was to evaluate two implant strategies on feedlot cattle performance. A total of 45 pens were randomly assigned to one of two implant strategies (two or three implants) in a randomized complete block experimental design. Each pen had 60 bulls with average initial weight of 277.6 ± 8.1 kg (range = 255–289 kg) and fed for 180 days. Bulls were implanted (100 mg trenbolone acetate–14 mg 17β-estradiol benzoate; Synovex® Choice) at the start of the experiment and re-implanted (200 mg trenbolone acetate–20 mg 17β-estradiol; Revalor® H) after 90 days (two implants; Synovex® Choice–Revalor® H) or at 60 and 120 days (three implants; Synovex® Choice–Revalor® H–Revalor® H) on feed. The measured performance indicators were the average daily gain (ADG), the dry matter intake (DMI), and the feed efficiency expressed as the gain-to-feed (G/F) ratio or the feed conversion ratio (FCR). Linear mixed model analyses included the treatment (implant strategy) and the covariate average initial weight as the fixed effects and block (2-week feedlot entry period) as the random effect. Treatment affected all performance measures (p < 0.01) except for ADG (p = 0.08). Pens of cattle administered two implants had greater DMI (9.54 ± 0.09 vs. 9.16 ± 0.10 kg/day p < 0.01) than pens of cattle administered three implants. Pens of cattle administered three implants had greater G/F ratio (0.160 ± 0.002 vs. 0.172 ± 0.002, p < 0.01) and smaller FCR (6.25 ± 0.08 vs. 5.82 ± 0.08, p < 0.01) than pens of cattle administered two implants. For cattle fed approximately 180 days in feedlot, a strategy with three instead of two implants increased the feed efficiency (~7.4%) without affecting the ADG, helping to improve profitability.